Medial Meniscus Posterior Root Tear A Comprehensive Literature Review - Oborski, Michał; Ohla, Jakub; Oborski, Krzysztof; Górski, Szymon; Okupniarek, Joanna; Ochwat, Maria; Bartosik, Michalina; Jętasiewicz, Igor; Piechocki, Paweł; Miarczyński, Jakub (Quality in Sport, 2025)
Introduction: medial meniscus posterior root tear (MMPRT) is an injury that leads to loss of the meniscus's biomechanical function and a sharp increase in cartilage load, which promotes the rapid development of knee osteoarthritis. It occurs mainly in older people, women, patients with obesity, low physical activity, and limb axis disorders, and in Asian populations it is additionally associated with habits requiring deep knee flexion. Due to nonspecific symptoms, the diagnosis of MMPRT is sometimes delayed, and magnetic resonance imaging remains the gold standard for diagnosis. Current treatment focuses on anatomical root repair techniques, which better protect the joint from degeneration than meniscectomy or conservative management. This paper summarizes the current knowledge on the pathophysiology, diagnosis, and treatment of MMPRT. Purpose Medial meniscus posterior root tears (MMPRTs) are increasingly common due to aging populations, sedentary lifestyles, and obesity. These injuries disrupt knee biomechanics, affecting joint stability and load distribution. This study reviews anatomy, biomechanics, and classification of MMPRTs, emphasizing early diagnosis and treatment to prevent joint degeneration. Materials and Methods…………………………………………………………………………... A review of current literature was conducted, focusing on diagnostic tools such as physical exams and imaging, with MRI identified as the gold standard. Injury classifications (e.g., LaPrade system) and criteria for conservative versus surgical management are discussed. Surgical techniques, including suture anchor repair and transtibial pull-out methods, were evaluated. Literature available in the PubMed and Google Scholar databases was searched using keywords. Results MRI remains the most accurate diagnostic tool, though its precision depends on imaging protocols. Surgical repair, especially anatomical techniques, yields better biomechanical and clinical outcomes than conservative approaches. Techniques like suture anchors and Mason-Allen stitches enhance stability and tissue regeneration. Non-operative methods may relieve symptoms but fail to restore anatomical function and can lead to progressive degeneration.